Rod‐Shaped Drug Particles for Cancer Therapy: The Importance of Particle Size and Participation of Caveolae Pathway. (12th April 2017) - He, Wei; Xin, Xiaofei; Li, Yongji; Han, Xiaopeng; Qin, Chao; Yin, Lifang
Abstract : It is disclosed how the sizes of rod‐shaped paclitaxel‐nanosuspensions (PTX‐Ns) that are less than 500 nm affect their in vitro and in vivo performances. A size reduction from 500 to 160 nm enhances the cellular uptake and subsequent cytotoxicity, due to the participation of caveolae‐mediated endocytosis; moreover, the ability of the PTX‐Ns to penetrate tumors is well correlated with the extent to which the caveolae pathway participates in cellular uptake, as their ability to target caveolae is markedly promoted as their size decreased to 160 nm. Also, the size reduction markedly alters the in vivo performance and tumor targeting. It is disclosed that via enhanced tumor penetration and retention but not simply increased tumor accumulation, size reduction of PTX‐Ns results in significant improvement in antitumor activities. Overall, this study highlights the importance of the size of the PTX‐Ns and the participation of caveolae‐mediated endocytosis in controlling their biological functions and will assist in the design and optimization of new nanosuspension formulations for disease therapy. Abstract : The size‐dependence of the performance of rod‐shaped paclitaxel‐nanosuspensions (PTX‐Ns) smaller than 500 nm (160, 300, and 500 nm) is investigated. This study highlights the importance of the size of rod‐shaped PTX‐Ns and the participation of caveolae‐mediated endocytosis in controlling their biological functions.